RESPON SISWA DALAM PEMBELAJARAN MATEMATIKA REALISTIK PADA TOPIK FUNGSI DI KELAS II SMPK SANTA AGNES SURABAYA - Partini, Haniek Sri (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
The aim of this study was to know the students’ responses for learning mathematics by using the realistic approach. Such students’ responses were important as reference for follow up in the implementation of mathematics realistic education applied at school. The study was descriptive research. The subjects of the study were students of Year 2, Santa Agnes Junior High School in Surabaya. Data were obtained by observing the teacher’s competence in managing instruction, observing students activities, an achievement test, and a student questionnaire. The research resulst showed that, out of a total of 53 students, more than 75% gave positive responses on the approach. They further showed that: (1) the students liked all of the learning components (83, 02%), (2) The students considered that all of the learning components were new things (79, 24%), (3) the students had a great interest to join the learning through the realistic approach (88, 68%), and (4) the students considered that the student books and student worksheets were understandable and interesting (83, 96%)